2018
DOI: 10.1111/add.14459
|View full text |Cite
|
Sign up to set email alerts
|

Age‐varying effects of cannabis use frequency and disorder on symptoms of psychosis, depression and anxiety in adolescents and adults

Abstract: Aims We tested the age‐varying associations of cannabis use (CU) frequency and disorder (CUD) with psychotic, depressive and anxiety symptoms in adolescent and adult samples. Moderating effects of early onset (≤ 15 years) and sex were tested. Design Time‐varying effect models were used to assess the significance of concurrent associations between CU and CUD and symptoms of psychosis, depression and anxiety at each age. Setting and Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
1
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 31 publications
5
73
1
6
Order By: Relevance
“…Such risks are not limited to the prenatal and perinatal periods: the onset of cannabis use normally occurs during adolescence, a period of continued brain maturation. Epidemiological data also suggest a greater frequency of use during the adolescent period is associated with psychiatric and substance use vulnerability (Silins et al, 2014;Leadbeater et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Such risks are not limited to the prenatal and perinatal periods: the onset of cannabis use normally occurs during adolescence, a period of continued brain maturation. Epidemiological data also suggest a greater frequency of use during the adolescent period is associated with psychiatric and substance use vulnerability (Silins et al, 2014;Leadbeater et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, psychotic-like experiences were associated with frequent cannabis use (β = 0.11, 95% CI 0.08-0.14), cannabis use disorder (β = 0.13, 95% CI 0.09-0.16), and current cannabis use (β = 0.07, 95% CI 0.04-0.10), even after adjustment for covariates (P < 0.05) [46]. Leadbeater and colleagues (2019) reported that more frequent cannabis use (β = 0.13, 95% CI 0.002-0.25, P < 0.05), as well as CUD (β = 0.51, 95% CI 0.01-1.01, P < 0.05), during adolescence were associated with psychotic symptoms at ages 22 and 23 [47]. Finally, Marconi and colleagues (2016) performed a meta-analysis of 18 studies reporting on the level of cannabis use that were published before 2014 and demonstrated that higher levels of cannabis use were associated with an increased risk for psychosis in all the included studies.…”
Section: Patterns Of Cannabis Usementioning
confidence: 99%
“…In fact, narcotic use was associated with a significantly higher burden of fatigue in patients with IBD [84]. Cannabis use, especially by young patients with IBD, is associated with depressive symptoms [85] as well as a motivational syndrome, which may be interpreted as fatigue.…”
Section: Concomitant Medicationsmentioning
confidence: 99%